Truly continuous low pH viral inactivation for biopharmaceutical process integration. Issue 5 (24th February 2020) - Martins, Duarte L.; Sencar, Jure; Hammerschmidt, Nikolaus; Flicker, Andreas; Kindermann, Johanna; Kreil, Thomas R.; Jungbauer, Alois
Abstract: Continuous virus inactivation (VI) has received little attention in the efforts to realize fully continuous biomanufacturing in the future. Implementation of continuous VI must assure a specific minimum incubation time, typically 60 min. To guarantee the minimum incubation time, we implemented a packed bed continuous viral inactivation reactor (CVIR) with narrow residence time distribution (RTD) for low pH incubation. We show that the RTD does not broaden significantly over a wide range of linear flow velocities—which highlights the flexibility and robustness of the design. Prolonged exposure to acidic pH has no impact on bed stability, assuring constant RTD throughout long term operation. The suitability of the packed bed CVIR for low pH inactivation is shown with two industry‐standard model viruses, that is xenotropic murine leukemia virus and pseudorabies virus. Controls at neutral pH showed no system‐induced VI. At low pH, significant VI is observed, even after only 15 min. Based on the low pH inactivation kinetics, the continuous process is equivalent to traditional batch operation. This study establishes a concept for continuous low pH inactivation and, together with previous reports, highlights the versatility of the packed bed reactor for continuous VI, regardless of the inactivation method. Abstract : Virus inactivation is essential for product safety however its implementation in continuous mode remains a challenge while the biopharma industry aims at continuous biomanufacturing. This work describes the full viral inactivation of two model viruses by low pH using a packed‐bed reactor with narrow residence time distribution as incubation reactor.This novel approach enables an truly continuous operation while being as effective as the current batch approach.